ANALISIS IMPLEMENTASI K3 PERKANTORAN MENURUT PERMENKES NO 48 TAHUN 2016 DI KANTOR RUMAH SAKIT UMUM SEMBIRING TAHUN 2024 - Ginting, Evfy Septriani (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
The implementation of office Occupational Health and Safety (OHS) in accordance with Ministry of Health Regulation No. 48 of 2016 is crucial to create a safe and healthy work environment. Without adhering to OHS standards, various issues such as increased risk of accidents, health problems, decreased productivity, and high healthcare costs can arise. Therefore, companies must ensure that all aspects of OHS are well-implemented to protect workers' well-being and enhance operational efficiency. The purpose of this study is to analyze the implementation of office OHS according to Ministry of Health Regulation No. 48 of 2016 at the Sembiring General Hospital Office in 2024. This research design uses a qualitative survey method with a descriptive phenomenology approach through the implementation of office occupational health and safety standards based on Ministry of Health Regulation No. 48 of 2016 at the Sembiring Hospital Office. The results of the study, based on the assessment data of office health and safety standard criteria in accordance with Ministry of Health Regulation No. 48 of 2016 and interview data with informants, show the following: the implementation of office health and safety standards was identified as moderately successful with a score of 48.39%, the implementation of office OHS policy was identified as less successful with a score of 34.52%, and the implementation of office occupational safety was identified as moderately successful with a score of 51.01%. This indicates that there are still many health and safety standard criteria that need to be fulfilled or optimized according to Ministry of Health Regulation No. 48 of 2016 on Office Occupational Health and Safety.